Compressibility and shear strength behaviour of peat soil in Sarawak - Zulkifli, Ahamad (Universiti Malaysia Sarawak, UNIMAS, 2005)
Peat soil are well known for their high water holding ability that make them highly compressible, low in shear resistance and low stability. In Sarawak, peat soil covers 13% of total land area. Therefore, the objective of this study is to investigate the compressibility and shear strength behaviour of peat soil in Sarawak.